2013
DOI: 10.1007/s10327-013-0440-z
|View full text |Cite
|
Sign up to set email alerts
|

Soft rot of root chicory in Hokkaido and its causal bacteria

Abstract: In August 2010, bacterial soft rot was found on root chicory (Cichorium intybus var. sativum) in Hokkaido, Japan. Severely infected plants in fields were discolored, had wilted foliage, and black necrosis of petioles near the crown. Wilted leaves subsequently collapsed and died, forming a dry, brown or black rosette. The root and crown became partially or wholly soft-rotted. Slimy masses on infected areas of roots, turned dark brown or black. Gram-negative, rod-shaped, peritrichously flagellated, facultatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Phenotypic diversity among P. c. subsp. odoriferum strains was also documented by Lan et al (2013). The atypical phenotypic features of some P. c. subsp.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Phenotypic diversity among P. c. subsp. odoriferum strains was also documented by Lan et al (2013). The atypical phenotypic features of some P. c. subsp.…”
Section: Discussionmentioning
confidence: 94%
“…P. c. subsp. odoriferum was first isolated in western Europe (Belgium, France, and Switzerland) (Gallois et al 1992;Samson et al 1980) and has since been reported in Poland, southern Europe (Gallelli et al 2009), Africa (Yahiaoui-Zaidi et al 2010), and Asia (Nazerian et al 2011;Thapa et al 2011;Lan et al 2013). Although P. c. subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout these countries, D . dianthicola has a wide host range [6, 12, 13], but potato is considered the main host [14, 15]. Infected potato plants exhibit wilting, dwarfing, and wet, oozy, black stems [3].…”
Section: Introductionmentioning
confidence: 99%
“…Carrot with soft rot disease. Adapted from Lindsey du Toit, Washington State University, North Carolina Cooperative Extension Sevice ( Lan et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%